2007
DOI: 10.1007/s00420-007-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lipid, hepatic, and thyroid parameters with serum perfluorooctanoate (PFOA) concentrations in fluorochemical production workers

Abstract: Objectives Perfluorooctanoic acid (PFOA) results in peroxisome proliferator mediated effects in rats and mice resulting in hypolipidemia but not in monkeys. Counterintuitive modestly positive associations between PFOA and cholesterol levels in production workers have been inconsistently reported. The purpose of this assessment was to examine this association in male workers who manufactured or used PFOA at three facilities. Methods Subjects were male employee voluntary participants of a fluorochemical medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
178
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(192 citation statements)
references
References 38 publications
10
178
2
Order By: Relevance
“…Exposure of Sprague-Dawley rats to PFOS and PFOA at a dose of 20 mg/kg resulted in hepatomegaly and severe histological changes of the liver, such as fatty degeneration, hepatocytic necrosis, and inflammatory cell infiltration 5) . Positive correlations of serum levels of PFOA with serum liver enzymes (γ -GTP, GOT or GPT) have been reported in several studies on fluorochemical workers with heavy exposure to PFOA or its related substance 32,33) but not in others 34,35) . Positive correlations were also observed between serum levels of PFOA or PFOS and hepatic enzymes (γ -GTP and/or GPT) in populations of the U.S. with high or background exposure to these PFCs 36,37) .…”
Section: Discussionmentioning
confidence: 85%
“…Exposure of Sprague-Dawley rats to PFOS and PFOA at a dose of 20 mg/kg resulted in hepatomegaly and severe histological changes of the liver, such as fatty degeneration, hepatocytic necrosis, and inflammatory cell infiltration 5) . Positive correlations of serum levels of PFOA with serum liver enzymes (γ -GTP, GOT or GPT) have been reported in several studies on fluorochemical workers with heavy exposure to PFOA or its related substance 32,33) but not in others 34,35) . Positive correlations were also observed between serum levels of PFOA or PFOS and hepatic enzymes (γ -GTP and/or GPT) in populations of the U.S. with high or background exposure to these PFCs 36,37) .…”
Section: Discussionmentioning
confidence: 85%
“…Modest associations between PFOA and THs (negative for free T4 and positive for T3) were reported in 506 PFOA production workers across three production facilities (Olsen & Zobel, 2007); there were no associations between TSH or T4 and PFOA, and the free TH levels were within the normal reference range. On the other hand, Metzer et al (Metzer et al, 2010) recently determined whether increased serum PFOA or PFOS concentrations are associated with thyroid disease in a general adult US population sample (n = 3,974 individuals ≥ 20 years of age from NHANES waves 1999-2000 (n = 1,040), 2003-2004 (n = 1,454), and 2005-2006 (n = 1,480)).…”
Section: Perfluoroalkyl Acidsmentioning
confidence: 84%
“…The renal clearance of PFOA and PFOS is negligible in humans, leading to reported half-lives in blood serum of 3.8 and 5.4 years for PFOA and PFOS, respectively (Olsen et al, 2007).…”
Section: Perfluoroalkyl Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on male workers involved in ammonium perfluorooctanoate production showed that mean serum PFOA, measured in 1993, 1995 and 1997, was 5000 (SD 12200) ng/ml, 6800 (SD 16000) ng/ml and 6400 (SD 14300) ng/ml [31]. Another study looking at male volunteers from the 3M company workforce at three different locations found mean serum PFOA and PFOS concentrations at 2.21 (SD 6.40) µg/ml and 1.05 (SD 0.97) µg/ml respectively [32].…”
Section: Introductionmentioning
confidence: 96%